2018
DOI: 10.3389/fphar.2018.00275
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 Inhibits Alcohol-Induced Hepatic Steatosis by Targeting Lipin1

Abstract: Alcoholic liver disease (ALD) is a global liver disease which characterized by liver inflammation, fatty liver, alcoholic hepatitis, or liver cirrhosis. Alcohol abuse is one of the main reasons for liver disease. Alcoholic fatty liver (AFL) disease is the early stage of ALD and associated with the excessive lipids accumulation in hepatocytes as well as oxidative stress. MicroRNA-203 (miR-203) is known to suppress the proliferation and metastasis of hepatocellular carcinoma, but the role in the progression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…In line with our results, a significant downregulation of miR-203 was also observed in mice after induction of alcoholic induced liver damage 39 . Out of the 4 miRNA candidates exclusively miR-132 was significantly upregulated after induction of all gastrointestinal diseases ( Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, a significant downregulation of miR-203 was also observed in mice after induction of alcoholic induced liver damage 39 . Out of the 4 miRNA candidates exclusively miR-132 was significantly upregulated after induction of all gastrointestinal diseases ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This study also suggested that a high level of miR-203 aggravates the cerulein induced cell injury through suppression of nuclear factor interleukin-3 38 . In line with our results, a significant downregulation of miR-203 was also observed in mice after induction of alcoholic induced liver damage 39 .…”
Section: Discussionsupporting
confidence: 91%
“…One species‐specific mature miRNA (ssa‐miR‐nov1‐5p) and the teleost‐specific miR‐462b‐5p were among the DE miRNAs, indicating they may have regulatory roles in the salmon lipid metabolism. All the remaining 10 evolutionary‐conserved DE miRNAs have been identified as miRNAs that are important in lipid metabolism and/or adipogenesis in other vertebrates (Ahn et al ., 2013; Arner & Kulyte, 2015; Chen et al ., 2014; Cheng et al ., 2018; Hu et al ., 2012; Shin et al ., 2014; Ye et al ., 2014). In most cases their particular functions have not been experimentally established but rather assumed from target gene predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Normal liver cell L02 line was obtained from the Laboratory Medicine of Chongqing Medical University (Chongqing, China) and cultured in RPMI 1640 (Gibco, United States) supplemented with 10% fetal bovine serum (Gibco, United States) and 100 U/ml Penicillin-Streptomycin Solution (Thermo Fisher Scientific, China). After reaching 50–60% confluence, L02 cells were stimulated with 100 mM alcohol medium for 48 h to construct the ALD cell model ( 9 , 13 ). All cells were grown at 37°C in a humidified incubator containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, miR-30b-5p promotes hepatocellular carcinoma (HCC) cell growth, proliferation, and metastasis by targeted inhibition of inositol polyphosphate phosphatase 1 expression ( 8 ). In ALD, over-expression of miR-203 decreases hepatic lipid accumulation by targeting the Lpin1 gene (Lipin1) ( 9 ). Silencing miR-21 decreases cytokine production and inflammatory responses in alcohol-induced hepatitis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%